The Influence of Complementary Feeding on Appetite and Growth Development in Children Aged 7-12 Months - Nur Anita; Ridda Nurchotimah; Wulan Wuliyanti; Retna Suzana; Dessy Oktaviana Sembiring; Wulan Sri Lestari; Yolanda Harumniti Susanto; Ria Rizkiya; Binti Roshada (Jurnal Penelitian Pendidikan IPA, 2024)
Complementary feeding (MP-ASI) is crucial for meeting the nutritional needs of infants aged 7-12 months, influencing their appetite and growth. Objective: This study evaluates the effects of MP-ASI on the appetite and growth of infants aged 7-12 months in 2024. A pre-post test design with 194 respondents assessed the impact of different types of MP-ASI on appetite and growth. All respondents received the same type of MP-ASI. Data were analyzed using univariate and bivariate analyses with SPSS. There was no statistically significant relationship between the type of MP-ASI given and weight gain. However, varieties such as spinach and eggs, and chayote and eggs, showed higher compliance with recommended nutritional standards (KPSP), indicating that MP-ASI type significantly influences adherence to these standards. Diverse MP-ASI positively affects the appetite and growth of infants aged 7-12 months. The study underscores the importance of MP-ASI variety and quality in child nutrition programs. Increasing parental education on the importance of MP-ASI variety is recommended to support optimal developmental potential in children.